ANALISIS PENGUKURAN TINGKAT KESIAPAN IMPLEMENTASI KNOWLEDGE MANAGEMENT (KM READINESS) PADA PT XYZ - Deden Artini (2020)
PT XYZ is a pioneer in the electronic transaction market in Indonesia, particularly the provider of infrastructure networks for banks. As an electronic transaction service provider whose mission is to provide efficient and effective electronic transaction services, PT XYZ creates highly flexible payment transaction products and services, applied to all levels of business units, ranging from activities upstream to activities downstream and accessible on a global scale and in real time. In addition, PT XYZ guarantees a high level of security, integrity and monitoring for all levels and types of transactions carried out. As a pioneer of key electronic transaction services, PT XYZ needs to understand the diverse needs of partners and customers. For this reason, staff must be able to share training and special consultations to accompany the management team to their partners. To be able to improve service to partners, it requires knowledge and experience of employees, so that knowledge is not lost, knowledge management is necessary to detect, capture, create and share. Not all organizations are successful in implementing knowledge management, so it is necessary to measure the level of readiness (readiness for knowledge management). This study aims to measure the level of preparation of PT XYZ for the implementation of knowledge management. The method used to measure the level of readiness consists in mapping the critical success factor of knowledge management (KMCSF) and in mapping the knowledge management infrastructure in the aspects of knowledge management (abstract, flexible and hard).